The motivations of elephant poachers in the Central African Republic - Leggett, Ted (Wildlife crime, 2018)
Why does a poacher decide to pull the trigger? Understanding this motivation is very important, because the illegal wildlife trade is different from other illicit markets, such as drug trafficking. With most forms of contraband, the social harm is felt when the commodity is used in the destination market. Wildlife is the reverse: the damage is done when the animal or plant is harvested at source. Interviews with poachers and community members in the Central African Republic reveal that price of ivory in destination markets is only one of a number of reasons why a hunter might choose to shoot an elephant. For local people, the meat may represent more value than the ivory, and some poachers may be motivated more by tradition than profit. These dynamics should inform the development of elephant protection strategies.